Effect of self-efficacy, competence and compensation in performance of financial manager on motivation as moderation - Putri, Kadek Dwiyani Ciptana; Sari, Maria Mediatrix Ratna; Ramantha, I Wayan; Budiasih, I Gusti Ayu Nyoman (International research journal of management, IT and social sciences, 2019)
This study aims to examine the effect of self-efficacy, competence, and compensation on the performance of financial management employees with motivation as moderating. The population in this study were all financial management employees at Udayana University in 2019. The study sample was determined by the nonprobability sampling method which obtained a total sample of 92 people. This study uses primary data and secondary data. The data analysis technique used in the study was multiple linear regression analysis and moderated regression analysis. The results showed that the variables of self-efficacy, competence, and compensation had a positive effect on the performance of financial management employees. Motivation does not moderate the effect of self-efficacy and competence on the performance of financial management employees. Motivation strengthens the effect of compensation on the performance of financial management employees.